A Historical Interaction between Artificial Intelligence and Philosophy - Zhang, Youheng (Teorie vědy, 2023)
This paper delves into AI development’s historical and philosophical dimensions while highlighting the symbiotic relationship between philosophy and AI from a technological perspective: philosophy furnishes foundational concepts, and AI supplies practical tools. The paper posits neurosymbolic AI as a solution to present challenges, sparking discussions encompassing both technical and philosophical considerations. Advocating a multidisciplinary approach calls for merging empirical AI insights with philosophy and cognition science to enrich our comprehension of intelligence and propel AI forward.